Solve Using the Square Root Property 6x^2-8x=0

Math
6×2-8x=0
Factor 2x out of 6×2-8x.
Tap for more steps…
Factor 2x out of 6×2.
2x(3x)-8x=0
Factor 2x out of -8x.
2x(3x)+2x(-4)=0
Factor 2x out of 2x(3x)+2x(-4).
2x(3x-4)=0
2x(3x-4)=0
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2x(3x-4)=0 by 2.
2x(3x-4)2=02
Simplify 2x(3x-4)2.
Tap for more steps…
Simplify terms.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2x(3x-4)2=02
Divide x(3x-4) by 1.
x(3x-4)=02
x(3x-4)=02
Apply the distributive property.
x(3x)+x⋅-4=02
Reorder.
Tap for more steps…
Rewrite using the commutative property of multiplication.
3x⋅x+x⋅-4=02
Move -4 to the left of x.
3x⋅x-4⋅x=02
3x⋅x-4⋅x=02
3x⋅x-4⋅x=02
Multiply x by x by adding the exponents.
Tap for more steps…
Move x.
3(x⋅x)-4⋅x=02
Multiply x by x.
3×2-4⋅x=02
3×2-4x=02
3×2-4x=02
Divide 0 by 2.
3×2-4x=0
3×2-4x=0
Factor x out of 3×2-4x.
Tap for more steps…
Factor x out of 3×2.
x(3x)-4x=0
Factor x out of -4x.
x(3x)+x⋅-4=0
Factor x out of x(3x)+x⋅-4.
x(3x-4)=0
x(3x-4)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x=0
3x-4=0
Set the first factor equal to 0.
x=0
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
3x-4=0
Add 4 to both sides of the equation.
3x=4
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3x=4 by 3.
3×3=43
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3×3=43
Divide x by 1.
x=43
x=43
x=43
x=43
The final solution is all the values that make x(3x-4)=0 true.
x=0,43
Solve Using the Square Root Property 6x^2-8x=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top